Countering tax crime in the European Union : benchmarking the OECD's ten global principles - Turksen, Umut (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This book seeks durable solutions for tax crime and is a great source for development of knowledge, policy and law on tax crime. The book uniquely blends current practice with new approaches to countering tax crime. With insights from the EU-funded project, PROTAX, which conducts advanced research on tax crimes, the book comparatively analyses the EU's tax crime measures and the Ten Global Principles (TGPs) on fighting tax crime by the Organisation for Economic Cooperation and Development (OECD). The study critically examines how the TGPs can serve as minimum standards for the EU to counter tax crime such as tax evasion and tax fraud. The study also analyses how the anti-tax avoidance package can be graduated to effectively fight tax crime in the EU. When escalated, the strengths of the EU tax crime measures and TGPs can form a fortress in which criminal law can be empowered to effectively mitigate tax crimes. The book will be particularly useful for end-user stakeholders such as tax policy makers, LEAs, professional enablers as well as academics and research students interested in productive interaction between tax, criminal and administrative laws"--
Introduction -- Defining tax crimes in the OECD and the EU -- Substantive principles -- Structural/procedural principles -- Relationship between criminal and administrative mechanisms -- Other components of the tax crime ecosystem -- Conclusion and recommendations.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Tax evasion -- Law and legislation -- European Union countries; Taxation -- Law and legislation -- European Union countries -- Criminal provisions; Taxation & duties law; Electronic books